GROWTH AND REPRODUCTION OF GELIDIELLA ACEROSA IN THE PALK BAY AND GULF OF MANNAR NEAR MANDAPAM - Rao, M Umamaheswara (Indian Journal of Fisheries, 2011)
Studies on growth and reiMrodusticn of Gelidiella acerosa growing in the Palk Bay near Ramsswaram and in the Gulf of Mannar near Pudumadam, have been carried out for three yeais from 1968 to 1970. Results obtained show that the plants of Ge/i- (/ie//(ti(icera.sa, which occur throughout the year, attain max •mum size in two seasons with a half yearly gruwth cycle and that the main growth season varies in the Palk Bay and Gulf of Mannar. The main growth season with peak number of large size fronds wasfoundbetweenE>ecember and April on the Palk Bay side and between July and August on the Gulf of Mannar side. The fruiting cycle of Gelidiella aceroia extends for a period of 7 to 9 months in a year and maximum nimiber of tetrasporic plants occur in the population jus t afteir the two peak growth periods. Considering the local changes in growth bshaviour, slow growth rate and the fruiting cycle, the period frcm December to April was found to be suitable for collecting Gelidiella acerosa in the Falk Bay and from July to August/September in the Gulf of Mannar.